2018
DOI: 10.1136/vr.104863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mutilations and other skin wounds in working donkeys in Tamil Nadu, India

Abstract: Wounds in working donkeys are a common and preventable welfare problem in many countries. Mutilations, iatrogenic injuries carried out by owners, are a particularly distressing welfare issue. However, little is known about their nature and prevalence. The project aim was to assess the general health and establish the prevalence, nature and severity of mutilations and other skin wounds in donkeys from several communities in Tamil Nadu, India, that were part of a donkey welfare initiative run by the Worldwide Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Donkeys play an important role in socioeconomic factors of the local population in Tanzania 16 ; however, data reporting on their welfare status are limited. There are a number of reports in the literature describing the prevalence of skin wounds and other welfare issues among working donkeys globally, 4 8 15 17–20 with a number focusing specifically on skin wounds either in the field 5 6 15 17 21–23 or under experimental conditions 24–26 . Much of the research on working donkey welfare has been focused in Ethiopia with prevalence of wounds varying between 37.9% and 79.4% 6 8 18 22 27 ; our findings on wound prevalence in this population of working donkeys concur with these values.…”
Section: Figuresupporting
confidence: 80%
See 1 more Smart Citation
“…Donkeys play an important role in socioeconomic factors of the local population in Tanzania 16 ; however, data reporting on their welfare status are limited. There are a number of reports in the literature describing the prevalence of skin wounds and other welfare issues among working donkeys globally, 4 8 15 17–20 with a number focusing specifically on skin wounds either in the field 5 6 15 17 21–23 or under experimental conditions 24–26 . Much of the research on working donkey welfare has been focused in Ethiopia with prevalence of wounds varying between 37.9% and 79.4% 6 8 18 22 27 ; our findings on wound prevalence in this population of working donkeys concur with these values.…”
Section: Figuresupporting
confidence: 80%
“…The working conditions and welfare status of each donkey were assessed using a number of animal‐based measures based on a previously published protocol 14 . In addition, skin wounds were assessed, described and recorded as reported previously by Rayner et al 15 . A skin wound was defined by the authors as “an injury to the skin which has resulted from a physical event, which causes compromise of, and disruption to, the skin, and may involve underlying subcutaneous and deep tissues”.…”
Section: Figurementioning
confidence: 99%
“…Lesions were recorded, with a high percentage of donkeys (66.67%) suffering from superficial knee lesions. In LMICs lesions are a commonly reported welfare issue in working equids [19,24,28]. The high prevalence of knee lesions found in this study in particular may be due to overloading, marshy and slippery streets and large quantities of garbage in the streets.…”
Section: Discussionmentioning
confidence: 61%
“…Mutilations are often performed in working equids for cultural, identification, husbandry or perceived therapeutic reasons [19,23]. Mutilations are a common welfare problem in working equids in many countries; for example one study conducted in India found that mutilations comprising nose-splitting, ear splitting and branding were the most common type of skin wound experienced by equids (comprising 62.8% of all wounds identified) [24]. Nostril slitting has been reported previously in Karachi [25,26,27]; this occurs due to the belief that the airways of animals in respiratory distress can be widened through the practice of creating a vertical slit from the ventral aspect of the nares up into the nostril, thereby alleviating dyspnoea during heavy work.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presence of many cauterizations was not surprising as they are commonly used to treat many camels' pathologies [41]. A higher prevalence of skin wounds, mainly due to incorrect applications of restraint tools, was also found in working equids in Egypt [42], India [43], and Nepal [34]. Training of the caretakers, better housing conditions and better management practices, such as the use of pads under the hobbles, could reduce the risk of injury in camels and improve their welfare level.…”
Section: Discussionmentioning
confidence: 99%